Influence of Educational Background on Stated Retreatment Choices for Suboptimal Fixed Prosthodontic Conditions - Riyadh Akeel, BDS, MDS, PhD (Journal of Prosthodontics, 2008)
The aim of this study was to compare the stated retreatment choices for defined, suboptimal fixed prosthodontic scenarios among groups of dental professionals with differing levels of education